AN ANALYSIS OF CODE MIXING USED IN RADITYA DIKA PODCAST (NGOMONGIN YOUTUBE BARENG DOVI JOVI) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The objective of this research was to find out the types of code mixing that appear on Raditya Dika podcast. This research focuses on code mixing that emerges on Raditya Dika podpcast. The research was descriptive qualitative method and the human research is the main instrument of this research. In collecting the data, this research utilized documentation method. In the types of code mixing, the highest type was intra-sentential of code mixing and the lowest type was involving a change of pronunciation. The researcher found 45 types of code mixing. The first is word with 9 data, phrase with 8 data and sentence with 25 data. In Intra-lexical, the researcher found 3 suffix.